2017
DOI: 10.1055/s-0037-1607055
|View full text |Cite
|
Sign up to set email alerts
|

IVIG-Associated Maternal Pancytopenia during Treatment for Neonatal Alloimmune Thrombocytopenia

Abstract: Background  Treatment for neonatal alloimmune thrombocytopenia (NAIT) primarily involves maternal administration of intravenous immunoglobulin (IVIG) therapy and prednisone according to protocols based on risk stratification. While IVIG is generally well tolerated, hematologic side effects are a potential complication. Case  We present the successful management of a rare complication of maternal pancytopenia following standard IVIG treatment. Diagnosis was made during routine obstetric exams. Management inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The most important maternal side effects are headache and flulike symptoms. One case of maternal pancytopenia was reported, in this case full blood count was normalized spontaneously 6 weeks after pregnancy [65,66]. Possible long-term effects on the development the immune system of children are not well known.…”
Section: Maternal Intravenous Immunoglobulins (Ivig) Administrationmentioning
confidence: 97%
“…The most important maternal side effects are headache and flulike symptoms. One case of maternal pancytopenia was reported, in this case full blood count was normalized spontaneously 6 weeks after pregnancy [65,66]. Possible long-term effects on the development the immune system of children are not well known.…”
Section: Maternal Intravenous Immunoglobulins (Ivig) Administrationmentioning
confidence: 97%
“…In a subsequent pregnancy, the woman will be offered close clinical follow-up, and most centers will start treatment with high-dose intravenous IgG (IVIg). In this context, it is prudent to mention that (1) IVIg is used off label for this indication as the efficacy in this condition has never been tested in a placebo-controlled clinical trial; (2) there is no international consensus of whom to treat, when to start treatment and dose of IVIg [ 38 ]; (3) there are significant side effects associated with IVIg treatment [ 39 , 40 , 41 , 42 ]; (4) this treatment is incredibly expensive and may easily exceed USD 100,000 per treated woman; (5) there is a worldwide shortage of IVIg [ 43 ]; and (6) treatment of one HPA-1a-immunized women requires tremendous donor efforts: 4.5 man-months of plasmapheresis [ 38 ].…”
Section: Fetal and Neonatal Alloimmune Thrombocytopeniamentioning
confidence: 99%
“…Administration of IVIG caused adverse events in pregnant women that were treated for FNAIT: severe hemolysis dependent on isoagglutinin content of IVIG preparation can occur [14,15]. Herrmann et al reported IVIG-related pancytopenia [16]. Blood group A mothers are more likely to develop anemia during IVIG treatment of FNAIT [17].…”
Section: Adverse Effects Of Ivig Prophylaxismentioning
confidence: 99%